Corrosion of reinforcing steel in strain hardening fiber reinforced cementitious composites - Ahmed, Shaikh; Mihashi, H. (ICMS Pty Ltd, 2010)
Corrosion of reinforcing steel is one of main deterioration mechanism in reinforced concrete structures. In this paper experimental results on the corrosion durability of cracked and uncracked reinforced concrete (RC) beams made with plain mortar and strain hardening fiber reinforced cementitious composites (SHFRCC) are presented. Three series of beams are considered. The first series is RC beams. While the second and third series consisted of SHFRCC beams containing polyethylene and hybrid steel-polyethylene fibers, respectively. Test results show that both cracked and uncracked beams containing SHFRCC materials exhibited better corrosion protection than that of plain mortar beams. Among all specimens the beam containing hybrid steel-polyethylene fiber SHFRCC exhibited the best corrosion protection.